2022
DOI: 10.1055/a-1988-2544
|View full text |Cite
|
Sign up to set email alerts
|

Make Bayley III Scores Comparable between United States and German Norms—Development of Conversion Equations

Abstract: Aim: Bayley Scales of Infant and Toddler Development (Bayley-III) determines scaled scores and converts these into composite scores. It was shown that applying of the German and the US manual leads to different results. This study aims to systematically analyze the differences between the US and German Bayley-III version and to develop conversion equations. Method: This simulation study generated a dataset of pairs of US and German Bayley III composite scores (cognitive: n=4,416, language: n=240,000, motor: n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The volumes of the TC connectivity-based clusters were mean (SD) mm 3 for frontal lobe (2047. 24 . We found that in 3 subjects, the volume of the occipital cluster was zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volumes of the TC connectivity-based clusters were mean (SD) mm 3 for frontal lobe (2047. 24 . We found that in 3 subjects, the volume of the occipital cluster was zero.…”
Section: Resultsmentioning
confidence: 99%
“…Raw scores were transformed into standard scores using the American norms. 24 Forty-four SBA newborns with mean (standard deviation) gestational age at birth of 35.5 (±1.8) weeks and at MRI of 37.97 (±1.13) weeks met these criteria and were enrolled in the analysis. The flow chart of how the final study population was reached is summarized in Figure 1.…”
mentioning
confidence: 99%
“…Each of these has a mean score of 100 and a standard deviation of 15. Raw scores were transformed into standard scores using the American norms ( Kosmann et al. 2023 ).…”
Section: Methodsmentioning
confidence: 99%